Determination of Stability Constants of UO2(II) Complexes with Thio Compounds by pH Metry - Ramana, V.V.; Yamuna, K.; Saraswathi, K. (Asian Journal of Chemistry, 2010)
The proton-ligand dissociation constant, log KL of sodium pentamethylene dithiocarbamate (Pipdtc), diethyl dithiocarbamate (Dedtc), ammonium pyrrolidine dithiocarbamate (Apdtc) and potassium ethyl xanthate (Xanthate) and metal-ligand stability constants log K1 and log K2 of their metal complexes with UO2(II) have been determined in 60% ethanol-water medium at 28ºC using Bjerrum Calvin pH titration technique as modified by Irving and Rosotti. The results obtained are compared with the data obtained for the other metal complexes of these ligands studied earlier in these laboratories. It was found that the proton ligand dissociation constants of these structurally similar thio compound and stability constants of their metal complexes decrease in the following order: Pipdtc > Dedtc > Apdtc > Xanthate